The influence of the topography of the Indian Peninsula on the low-level circulation of the summer monsoon - GADGIL, SULOCHANA; SIKKA, D. R. (MAUSAM, 1978)
The effect of the topographic complex formed by the Western Ghats along the west coast of south India and the adjoining Deccan plateau to their east, on the low-1evel circulation of the summer monsoon and its associated rainfall are investigated. Quasi-geostrophic models of flow of a homogeneous fluid in the presence of obstacles in a rotating system are applied to identify two features of the low-level circulation which are suggested to be manifestations of the influence of the topographic feature considered. These are the southward direction of the low-level isobars on the Peninsula and the prominent trough on the Bay of Bengal. The nature of variation of these features as a response to change in conditions upstream of the topography is described. The spatial variation of the rainfall over the Peninsula predicted by assuming it to be proportional to the vorticity compares favourably with the observed variation of the seasonal rainfall.